Przeobrażenia w strukturze stosunków pracy w przedsiębiorstwach - Gach, Daniel; Pietruszka-Ortyl, Anna (The changes of the personal structure in the enterprises, 2006)
In the article, changes that occur in organization's recruitment policy are presented. The starting point of the considerations is the description of current tendencies in recruitment, namely - limitation of employee's numbers that operate on the basis of the full contract of employment and constantly work in the factory or office. The authors have presented concept of enterprise as the clover and model of "the bull's eye". In the next part perfect employee's competency profile is shown. The article is summed up by the deliberations about change in the client treatment - as the important part of the organization's human capital.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 615-623